2021
DOI: 10.1111/jth.15490
|View full text |Cite
|
Sign up to set email alerts
|

Persistent endotheliopathy in the pathogenesis of long COVID syndrome

Abstract: Background Persistent symptoms including breathlessness, fatigue and decreased exercise tolerance have been reported in patients after acute SARS‐CoV‐2 infection. The biological mechanisms underlying this ‘ Long COVID ’ syndrome remain unknown. However, autopsy studies have highlighted the key roles played by pulmonary endotheliopathy and microvascular immunothrombosis in acute COVID‐19. We hypothesized that endothelial cell activation may be sustained in convalescent CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
244
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(260 citation statements)
references
References 32 publications
8
244
0
8
Order By: Relevance
“…Altered endothelial dysfunction-related microRNAs were found in plasma from ME/CFS patients recently [ 5 ]. In Covid-19 infection the endothelium is severely affected and the disturbance seems to persist in post-Covid Syndrome (PCS) [ 8 , 12 , 20 , 23 , 34 ]. Particularly the finding of severe endothelial affection in Covid-19 and the persisting endothelial dysfunction corroborates our hypothesis of a role of endothelial and vascular dysfunction in the pathogenesis of PCS.…”
Section: Decreased Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…Altered endothelial dysfunction-related microRNAs were found in plasma from ME/CFS patients recently [ 5 ]. In Covid-19 infection the endothelium is severely affected and the disturbance seems to persist in post-Covid Syndrome (PCS) [ 8 , 12 , 20 , 23 , 34 ]. Particularly the finding of severe endothelial affection in Covid-19 and the persisting endothelial dysfunction corroborates our hypothesis of a role of endothelial and vascular dysfunction in the pathogenesis of PCS.…”
Section: Decreased Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…From mechanistic points of view, it remains unclear whether dysregulated immune response is the primary pathogenic mechanism in severe COVID-19, although in the acute phase of severely ill patients with COVID-19, anti-inflammation agents are effective. In a retrospective observational study, persistent endotheliopathy with increased levels of factor VIII, VWF, and thrombomodulin, compared with healthy subjects, was observed in convalescent COVID-19 patients, independent of ongoing acute phase response or NETosis [ 215 , 216 ]. The hypercoagulable state observed in severe COVID-19 patients was associated with elevated levels of factor VIII and VWF, suggesting the involvement of endothelial cells [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear which of the two mechanisms mainly contribute to activation of the kallikrein–kinin system in COVID-19. It was reported that systemic factor XIIa levels were not elevated in patients with long COVID-19 syndrome, compared with healthy subjects, while factor VIII and VWF levels were higher in these patients, suggesting that ACE2 internalization might be the main contributor to activation of the kallikrein–kinin system in COVID-19 [ 215 ]. ACE2 decoys and bradykinin inhibitors could be therapeutic candidates for COVID-19 that target endothelial dysfunction, in addition to statin and nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests a high prevalence of long-COVID, a clinical constellation that is difficult to grasp since most routine clinical tests are inconspicuous even in highly symptomatic patients. Based on blood biomarker assessment, Fogarty et al [ 10 ] have just recently proclaimed a potential role of persistent endotheliopathy in long-COVID. Future prospective studies combining PAT assessment with laboratory and clinical patient data will help to investigate a potential association of endothelial dysfunction with long-COVID.…”
mentioning
confidence: 99%